The inter and intra Relationship between Economics, Administrative sciences and Social sciences disciplines - Noureddine Benlagha; Wael Hemrit (Research in Social Sciences and Technology- OpenED Network, 2018)
The aim of this paper is to present a framework proposal for measuring the extent to which the six disciplines (Economic, Administrative sciences, Finance and investment, Accounting, Banking and Insurance and risk management) reach out to spaces shared with other disciplines at the College of Economic and Administrative sciences in the University of Al Imam Mohammad Ibn Saud Islamic University. First, in the Intraspecific Relationship measurement, our results indicate that these disciplines are far from having a dependence with History, Politics, Ethics and Sociology. Second, we find that the studies of the Sharia are flourishing and the economic and administrative sciences courses in the field are being defended. In the field study of Interspecific Relationships, our results indicate a deficiency of the relationship between the related disciplines in different manners. Economic and Administrative sciences disciplines have, especially, the lowest degree of openness, compared to the rest of disciplines.